Mediation in criminal proceedings: legal regulation in Ukraine and foreign experience of application - Motliakh, O.; Bezusyi, V. V.; Безусий, В. В.; Chudnovskyi, O.; Burlakov, S.; Shevchuk, H. (Cuestiones Políticas. – 2020. – Vol. 38, № Especial (2da parte). – P. 410-425, 2020)
Метою статті є дослідження задумів використання інституту медіації у кримінальному судочинстві європейських країн для впровадження позитивного досвіду в українське законодавство. Тема дослідження – інститут медіації у кримінальному процесі. У дослідженні використовувалися такі наукові методи: діалектичний, формально-логічний та юридичний, системно-функціональний, порівняльно-правовий, юридичний та інші модельовані методи. Ми досліджуємо кон’юнктуру нормативно-правового регулювання медіації в кримінальному судочинстві в Україні, а також практику її впровадження, яка порівняно з іншими європейськими державами є більш ніж скромною. Тому ми використовуємо досвід таких країн, як Німеччина, Польща, Велика Британія. Зроблено висновок, що враховуючи успішне функціонування інституту медіації в більшості країн, ми пропонуємо наслідувати цю позитивну практику та прийняти окремий закон «Про медіацію» в Україні. Встановлено, що основним правом для законодавчого оформлення медіації в Україні є відсутність інформації про наявність такого способу вирішення кримінальної справи.

The purpose of the article is to study those conceived of the use of the mediation institution in the criminal proceedings of European countries to implement positive experience in Ukrainian law. The theme of the study is the institution of mediation in criminal proceedings. The following scientific methods were used in the research: dialectical, formal and logical, and legal, system and functional, comparative and legal, legal and other modeled methods. We study the concetorities of the regulation and legal of mediation in criminal proceedings in Ukraine, as well as the practice of its implementation, which is more than modest with other European states. Therefore, we draw on the experience of countries such as Germany, Poland, and the United Kingdom. It is concluded that, given the successful functioning of the mediation institution in most countries, we propose to emulate this positive practice and a separate law “On Mediation” in Ukraine. It is established that the main right for the legislative registration of mediation in Ukraine is the lack of information on the existence of such a way of resolving a criminal case.

Цель статьи состоит в том, чтобы изучить использованиt института медиации в уголовном судопроизводстве европейских стран для имплементации положительного опыта в украинском законодательстве. Темой исследования является институт медиации в уголовном судопроизводстве. В исследовании использовались следующие научные методы: диалектический, формально-логический, юридический, системно-функциональный, сравнительно-правовой, юридический и другие моделирующие методы. Мы изучаем особенности регулирования и правовой медиации в уголовном судопроизводстве в Украине, а также практику ее реализации, которая более чем скромна с другими европейскими государствами. Поэтому мы опираемся на опыт таких стран, как Германия, Польша, Великобритания. Делается вывод о том, что, учитывая успешное функционирование института медиации в большинстве стран, мы предлагаем перенять эту положительную практику и принять отдельный закон «О медиации» в Украине. Установлено, что основным правом законодательного оформления медиации в Украине является отсутствие сведений о существовании такого способа разрешения уголовного дела.
Mediación en procesos penales: regulación legal en Ucrania y experiencia de aplicación extranjera
Mediation in criminal proceedings: legal regulation in Ukraine and foreign experience of application / Motliakh Oleksandr, Bezusyi Vadym, Chudnovskyi Oleksandr, Burlakov Serhii, Shevchuk Hennadii // Cuestiones Políticas. – 2020. – Vol. 38, № Especial (2da parte). – P. 410-425. – DOI: https://doi.org/10.46398/cuestpol.382e.32.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; publikatsii u WoS; Україна. Ukraine. Украина; mediation in criminal proceedings; mediation; criminal proceedings; restorative justice; legislative regulation; european mediation experience; comparative law; порівняльне правознавство; медіація; кримінальне провадження; уголовное производство; медиация